Manajemen Pendidikan Karakter Berbasis Sekolah Era Digital di Indonesia - Astuti, Nuryani Dwi; Marzuki, Marzuki; Hajaroh, Mami; Prihatni, Yuli; Kusumawardhani, Ratih; Hartono, Arif; Setiawan, Ari; Aziz, Mohd Kasturi Nor Abd (Jurnal Pendidikan Karakter, 2025)
This research aims to reveal the importance of character education management in shaping students' ideal personalities, especially in the digital era. This research uses library research method to analyze various literature sources related to character education management. Data sources are journals, proceedings, and books. The data collection technique focuses on in-depth search and analysis of text or literature sources. The results show that character education management requires detailed planning, efficient organization, effective implementation, and careful supervision. The implementation of character education in the digital era requires an innovative and synergistic approach between various educational components. Concrete examples of the application of character education management in the digital era include setting digital character education goals, dividing tasks and resources, implementing programs through digital technology, and monitoring and evaluating programs regularly. Thus, character education integrated with digital technology can help form a young generation with good character, faith, honesty and discipline, and be able to have a positive impact on the surrounding environment. This research emphasizes the importance of character education as an effective means of forming morally and spiritually complete individuals.